2015
DOI: 10.1111/josi.12096
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity Threat in Response to Stereotypic Film Portrayals: Effects on Self‐Conscious Emotion and Implicit Ingroup Attitudes

Abstract: Disadvantaged ethnic groups are often portrayed stereotypically in film, but little is known about how such portrayals affect members of those groups. Two experiments examined the affective and attitudinal reactions of Mexican and European Americans to stereotypic film clips of Latinos. Results of Study 1 revealed that stereotypic films cue negative affect among Mexican Americans, regardless of the realism of the portrayals. In Study 2, both Mexican and European Americans felt more self‐conscious when another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 30 publications
4
74
1
1
Order By: Relevance
“…This is significant considering that when minorities are represented in media they are either under represented or negatively represented (Mastro, 2009). Previous research reveals that negative media representations have detrimental consequences on minorities' self-esteem and negative emotional responses (e.g., Schmader et al, 2015). Results from the present study reveal that negative media messages may also affect intergroup relations such as desire to avoid majority members.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…This is significant considering that when minorities are represented in media they are either under represented or negatively represented (Mastro, 2009). Previous research reveals that negative media representations have detrimental consequences on minorities' self-esteem and negative emotional responses (e.g., Schmader et al, 2015). Results from the present study reveal that negative media messages may also affect intergroup relations such as desire to avoid majority members.…”
Section: Discussionmentioning
confidence: 50%
“…A consideration of the minority members' perspective is important as it helps to provide a more complete understanding of the role of media in intergroup relations. The limited work that does exist in this domain tends to focus on minority members' self and group perceptions rather than identity management strategies that can restore a positive view of the threatened identity (e.g., Abrams & Giles, 2007;Banjo, 2013;Ortiz & Behm-Morawitz, 2015;Rivadeneyra et al, 2007;Schmader et al, 2015). For example, Banjo (2013) found that African Americans were especially concerned about Black media stereotypes influencing Whites' opinion of African Americans when they watched the movie with a majority White, relative to Black, audience.…”
Section: Negative Media Representations As Social Identity Threatsmentioning
confidence: 92%
See 2 more Smart Citations
“…Research on media effects suggests that negative, stereotypical portrayals of one's own group represent threats to the self‐esteem of racial or ethnic (Banjo, ; Fryberg, Markus, Oyserman, & Stone, ; Fujioka, ; Martins & Harrison, ; Schmader, Block, & Lickel, ) and religious (Ibrahim & Abdel Halim, ; Saleem & Ramasubramanian, ) minority audiences. Muslim minority members may be particularly vulnerable to negative media representations, as they frequently face discrimination in Western societies (Martinovic & Verkuyten, ; Sirin et al, ) and are often portrayed in negative and stereotypical ways in the mainstream media (e.g., Alsultany, ; Dixon & Williams, ; Saleem & Anderson, ; Saleem, Prot, Anderson, & Lemieux, ; Saleem, Yang, & Ramasubramanian, ).…”
mentioning
confidence: 99%